2001
DOI: 10.1046/j.1365-2540.2001.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal genes in Coregonid fishes (Coregonus lavaretus, C. albula and C. peled) (Salmonidae): single and multiple nucleolus organizer regions

Abstract: Major rDNA loci, i.e. nucleolus-organizing regions (NORs), were assigned using chromomycin-A3 (CMA3) staining followed by sequential silver (Ag) staining and in situ hybridization (ISH) with a rDNA probe to the chromosomes of the European whitefish (Coregonus lavaretus), the peled (Coregonus peled) and the vendace (Coregonus albula), three closely related coregonine salmonid fishes. One pair of NOR-bearing chromosomes was found in the peled karyotype. Multichromosomal, but stable, locations of rDNA sites on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
(29 reference statements)
1
22
1
Order By: Relevance
“…In some cases such relation is merely presumed, i.e. in coregonid species Jankun et al (2001) found the same number of CMA 3 -stained sites and FISH signals on apparently the same chromosome pairs. From then on the authors assumed a positive correlation (Jankun et al, 2003b).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some cases such relation is merely presumed, i.e. in coregonid species Jankun et al (2001) found the same number of CMA 3 -stained sites and FISH signals on apparently the same chromosome pairs. From then on the authors assumed a positive correlation (Jankun et al, 2003b).…”
Section: Discussionmentioning
confidence: 98%
“…It is commonly accepted that major rDNA clusters on fish chromosomes can also be identified by fluorescent staining with chromomycin antibiotic (CMA 3 ) that binds preferentially to GC-rich chromatin segments characteristic of rDNA sites of teleostean fishes (e.g., Mayr et al, 1985;Amemiya and Gold, 1986;Schmid and Guttenbach, 1988). Correlations between Ag-NORs and CMA 3 positive sites have been reported for several fish species (e. g., Sola et al, 2000;Jankun et al, 2001Jankun et al, , 2003aRabova et al, 2001Rabova et al, , 2003.…”
Section: Copyright © 2005 S Karger Ag Baselmentioning
confidence: 99%
“…Polymorphisms of the NOR are relatively common in fish, especially in the Salmonidae and Characidae families, which show both intra-and inter-individual variation of these regions (Galetti Jr., 1998;Castro et al, 1996Castro et al, , 2001Jankun et al, 2001;Santi-Rampazzo et al, 2008). Although inter-individual variations of NORs are considered to be relatively rare in fish, some have been identified in Leporinus friderici (Galetti Jr. et al, 1995), Serrapinnus notomelas (Santi-Rampazzo et al 2008), in the genus Symphysodon (Gross et al, 2010), R. lanceolata (Porto, 2012), and in L. cataphracta (present study).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the ancestral number of rDNA clusters in the Eyprepocnemidinae is restricted to one to three of the four smallest autosomes (M 8 -S 11 ). In some animal groups, for example, fishes, the existence of a single rDNA cluster is considered a plesiomorphic character (see Jankun et al, 2001), although many examples of multichromosomal location of rDNA have been described (see Castro et al, 2001). In the Eyprepocnemidinae grasshoppers analysed here, the most conserved rDNA cluster is that located on the S 9 chromosome, which is present in four of the five species analysed.…”
Section: Discussionmentioning
confidence: 99%